2022
DOI: 10.1038/s41598-022-15903-2
|View full text |Cite
|
Sign up to set email alerts
|

Light enhanced the antimicrobial, anticancer, and catalytic activities of selenium nanoparticles fabricated by endophytic fungal strain, Penicillium crustosum EP-1

Abstract: Selenium nanoparticles (Se-NPs) has recently received great attention over owing to their superior optical properties and wide biological and biomedical applications. Herein, crystallographic and dispersed spherical Se-NPs were green synthesized using endophytic fungal strain, Penicillium crustosum EP-1. The antimicrobial, anticancer, and catalytic activities of biosynthesized Se-NPs were investigated under dark and light (using Halogen tungsten lamp, 100 Watt, λ > 420 nm, and light intensity of 2.87 W m−2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 78 publications
2
54
0
Order By: Relevance
“…The current examination revealed that the MIC value of ciprofloxacin was 25 μg ml –1 against Gram-negative tested pathogens, while the MIC values of penicillin G and ketoconazole against Gram-positive and fungal pathogens, respectively, were perceived at 50 μg ml –1 . These findings are consistent with previous studies confirming that the elimination of fungal infections may require intensive doses, as they have a very solid cell wall containing chitin and glucan and is completely different from the bacterial cell wall 71 , 72 . Overall, it can be concluded that the antimicrobial activity of functionalized chitosan with thiadiazole derivative was increased compared to unmodified compound.…”
Section: Resultssupporting
confidence: 93%
“…The current examination revealed that the MIC value of ciprofloxacin was 25 μg ml –1 against Gram-negative tested pathogens, while the MIC values of penicillin G and ketoconazole against Gram-positive and fungal pathogens, respectively, were perceived at 50 μg ml –1 . These findings are consistent with previous studies confirming that the elimination of fungal infections may require intensive doses, as they have a very solid cell wall containing chitin and glucan and is completely different from the bacterial cell wall 71 , 72 . Overall, it can be concluded that the antimicrobial activity of functionalized chitosan with thiadiazole derivative was increased compared to unmodified compound.…”
Section: Resultssupporting
confidence: 93%
“…The elemental analysis of NP5-AgNPs exhibited a prominent silver peak at 3 keV, indicating that silver is the primary element in the fabricated AgNPs. The weaker peaks of carbon, oxygen, potassium, silicon and other recorded elements in the nanoparticles are due to fungal bioactive metabolites, such as proteins and enzymes, which cap and impart the stability of AgNPs [ 42 ]. Pallavi et al [ 43 ] also found that biosynthesized AgNPs from the Streptomyces hirsutus strain SNPGA-8, exhibit prominent silver peak at 3 keV with 22.24% silver in the synthesized NPs along with other trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…This activity provides antibiotics against pathogens and microorganisms such as C. gloeosporioides , E. coli , B. subtilis , S. aureus , and B. cereus that can cause food defects. Furthermore, antimicrobial is divided into antifungal and antibacterial [ 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Helvolic acid ( 4 ) was tested against fungi such as B. cinerea , A. solani , A. alternata (Fries) Keissler, C. gloeosporioides , F. solani , F. oxysporum f. sp.…”
Section: Bioactivity Of Secondary Metabolites Isolated From Endophyti...mentioning
confidence: 99%